Approaches to the study of progress, monitoring of sports training and selection of athletes in a sports context - Guba, V. P.; Levushkin, S. P.; Lyakh, V. I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to systematise the research of domestic specialists on the development, control of physical abilities and their assessment in the selection process.